2017
DOI: 10.1093/hmg/ddx194
|View full text |Cite
|
Sign up to set email alerts
|

Tea and coffee consumption in relation to DNA methylation in four European cohorts

Abstract: Lifestyle factors, such as food choices and exposure to chemicals, can alter DNA methylation and lead to changes in gene activity. Two such exposures with pharmacologically active components are coffee and tea consumption. Both coffee and tea have been suggested to play an important role in modulating disease-risk in humans by suppressing tumour progression, decreasing inflammation and influencing estrogen metabolism. These mechanisms may be mediated by changes in DNA methylation. To investigate if DNA methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 74 publications
0
20
3
Order By: Relevance
“…In our study, EWAS meta-analysis of tea consumption showed only two suggestive associations, despite having the advantage of much larger sample size and good statistical power compared to the previously published EWA study 20 . In the earlier study, Ek et al reported two CpGs associated with tea consumption in women, nevertheless, those CpGs were not replicated in our study.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In our study, EWAS meta-analysis of tea consumption showed only two suggestive associations, despite having the advantage of much larger sample size and good statistical power compared to the previously published EWA study 20 . In the earlier study, Ek et al reported two CpGs associated with tea consumption in women, nevertheless, those CpGs were not replicated in our study.…”
Section: Discussioncontrasting
confidence: 75%
“…Here, we postulate that alteration of DNA methylation via coffee or tea consumptions is an underlying mechanism linking the intake of these beverages to health outcomes. Previous epigenome-wide association studies (EWAS) have reported suggestive association of a few CpGs with tea or coffee consumptions 20,21 ; however, these studies were limited by modest sample sizes. In the present study, we conducted large-scale EWAS meta-analyses on coffee and tea consumptions in 15,789 participants of European and African-American ancestries from 15 cohort studies.…”
Section: Introductionmentioning
confidence: 99%
“…it mainly by the death of dopamine-producing neurons in our brain [86][87][88][89][90][91] Coffee consumption protects against 65 or more aged people from Alzheimer's disease and dementia. It lower 65% risk of Alzheimer's disease…”
Section: Health Benefit Of Coffee Consumption Description Of Action Smentioning
confidence: 99%
“…A recent epidemiological study was conducted to evaluate the in vivo effects of green tea consumption on human DNA. The analysis revealed that 28 regions were differentially methylated in relation to green tea consumption, but only in women [21]. This indicates that some genomic regions are relatively more sensitive to DNA demethylating compounds, which are known to act through several mechanisms.…”
Section: Discussionmentioning
confidence: 95%